2000
DOI: 10.1111/j.1540-8159.2000.tb00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐of‐Life of Pacemaker Patients: A Reappraisal of Current Instruments

Abstract: Current clinical practice permits the use of single chamber ventricular or dual chamber pacemakers. However, it is not known which type of pacemaker results in superior clinical and patient outcomes. This is of growing importance because of the higher costs and increased risk of technical failures of dual chamber pacemakers. Patient outcomes can be assessed with quality of life questionnaires, but it is unclear which questionnaires are valid for use in pacemaker patients. This article reappraises studies on qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…17 Studies included were predominantly observational and a much wider range of measures was identified than has been used in the trials of dual-and single-chamber pacemakers reported later in this assessment. Disease-specific and generic measures have been used to measure quality of life in this population as well as new measures constructed from pre-existing scales for the specific purpose of measuring the impact of cardiac pacing on quality of life.…”
Section: Impact: Disability and Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…17 Studies included were predominantly observational and a much wider range of measures was identified than has been used in the trials of dual-and single-chamber pacemakers reported later in this assessment. Disease-specific and generic measures have been used to measure quality of life in this population as well as new measures constructed from pre-existing scales for the specific purpose of measuring the impact of cardiac pacing on quality of life.…”
Section: Impact: Disability and Quality Of Lifementioning
confidence: 99%
“…Narrative, editorial, expert opinions, nonsystematic reviews (31) Preclinical studies (blood haemodynamics, blood pressure, blood compounds, etc.) (112) Studies that do not report relevant outcomes, or for non-relevant underlying disease (10) Studies with less than 48 hours' follow-up (17) Other (non-English language, abstracts, trial details reported elsewhere) (20) Studies included = 46 Studies excluded = 324 …”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommended generic measures include the Short Form Questionnaire-36 items (SF-36), a health questionnaire with 36 questions, which looks at functional health, general well-being and physical and mental health. 15 The Karolinska Questionnaire, 16 which has been validated in patients paced for bradyarrhythmia, contains 16 questions on cardiovascular symptoms relevant to pacemaker patients. The Specific Activity Scale (SAS) 17 is another disease-specific questionnaire for the functional classification of patients with cardiovascular disease (CVD).…”
Section: Measurements Of Diseasementioning
confidence: 99%
“…For patients with pacemakers, the literature recommends using a specific questionnaire related to general health issues contained in a generic questionnaire [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%